Skepticism in Walter Raleigh’s Poetry - Mahmood, Essam (Al-Adab Journal, 2025)
The present paper focuses on one major issue. It is the fear of doubtfulness which the poet suffers from. Walter Raleigh was a great poet of the sixteenth century who composed and produced poems that reveal the misery of life at that time. Because he was favourite man to Queen Elizabeth, no one dares to silence him. After the death of the queen, he was put in jail for the rest of his life. In jail, he composed some beautiful poems revealing his gloomy aspects of his desperate life inside the jail. So, this paper aims at investigating the concept of skepticism which is clearly discussed and highlighted in Raleigh’s poetry.